Transcriptome Analysis of the Phytophthora Infestans Induced Stress-Response in Different Potato Cultivars - Taller, János; Nagy, Erzsébet; Idogwu, Esther Ijeoma; Wolf, István; Polgár, Zsolt; Frank, Krisztián (GEORGIKON FOR AGRICULTURE, 2024)
Late blight, caused by the oomycete fungus Phytophthora infestans (Mont.) De Bary, is one of the most dangerous diseases of potatoes. A number of resistance genes have been identified in wild Solanum species, of which 11 race-specific P. infestans resistance genes derived from Solanum demissum are the most widely used in potato improvement. Our previous analyses have shown that most of the 11 R genes are present in cultivar White Lady (WL). In the present research program, in addition to WL, which has high resistance to late blight, we used the cultivar Kastia, described by Gergely (2004) as having good horizontal resistance, and a susceptible cultivar, Sárvári borostyán, to compare by transcriptome analysis their responses to P. infestans inoculation. The transcriptome analysis was performed on purified RNA from leaf samples taken before inoculation with P. infestans isolate MP-1548 (control) and 18, 24, 48 and 72 h after inoculation. The infection experiment demonstrated the expected resistance of WL and susceptibility of Sárvári borostyán, but Kastia showed the typical symptoms of Phytophthora infection. Short reads of each RNA sequence were aligned to the long read transcriptome of an in vitro White Lady plant and over 100 000 transcripts per sequencings were identified. The stress response of the three cultivars to P. infestans infection was characterized by comparing these gene collections. Our analyses revealed overall differences in the response of resistant and susceptible cultivars to P. infestans inoculation.
Keywords: Phytophthora infestans; potatoe; transcriptome analysis; resistance